Synthesis and Characterization of Nano Composite BiOI-Allophane Gamalama Volcanic Soil - Nur A Limatahu; Indra Cipta; St Hayatun Nur; Indriana Kartini; Yateman Aryanto (ICETIA, 2016)
Nano composite BiOI-Allophane was successfullysynthesized by using hydrothermal reaction method. Theallophane was isolated from Gamalama volcanic soil by usingHenmi method which modified in accordance with theavailability of laboratory equipments. Isolated allophane wasadded into mixtures of 5 mmol Bi(NO3)2 and 5 mmol KI. Acidityof mixtures was maintained at pH 7 by using NH4OH 2M. Themixtures was then put into hydrothermal reactor and heated at180oC for 24 hours. The composite was characterized by usingFTIR, XRD, SEM, and TEM. FTIR spectra shows vibrationsthose are characteristic of BiOI and aluminosilica. XRDdifractogram, SEM and TEM were confirmed that BiOI bindedin allophane framework. The size and the form of BiOIallophanecomposite is heterogeneous nano-ballabout 5 nm.